2018
DOI: 10.17265/2159-5828/2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization and Bio-Control Activities of Bacillus Subtilis from the Fermented Soybean in Cambodia

Abstract: The objective of this study was to isolate Bacillus subtilis produced Bacteriocin from Khmer traditional fermented soybean to control the growth of pathogenic bacteria from 120 SIENG samples from 9 different local open markets in Phnom Penh, 1 local open market and 2 local producers in Kandal province in Cambodia. 119 out of 120 samples were positive with Bacillus subtilis strains. Fifteen of these isolated strains exhibited antimicrobial activity to Lactobacillus plantarum by agar well diffusion assay and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The reports by the Asian Foundation and the Overseas Development Institute states that the problem with waste management is two-pronged, namely the amount of waste produced as well as the method of collecting and disposing of them ("The problem with landfill", 2013). The Cambodian government chose to landfill as its main method of disposing of waste across the country and Dangkao land allocated for this purpose in Phnom Penh, for instance, was projected to last 25 years but about five years into its use, between 2009 and 2014, about half of the land had been filled already and environmental experts further projected the land to last another five years until 2019 (Sopheap, Inatsu, Thavrak, & Borarin, 2016). Investigations showed that the Cambodian government signed a 50-year contract plan with CINTRI Cambodia Ltd., a private waste management company to take charge of waste collection, management, and disposal.…”
Section: Waste Management and Pollution In Cambodiamentioning
confidence: 99%
“…The reports by the Asian Foundation and the Overseas Development Institute states that the problem with waste management is two-pronged, namely the amount of waste produced as well as the method of collecting and disposing of them ("The problem with landfill", 2013). The Cambodian government chose to landfill as its main method of disposing of waste across the country and Dangkao land allocated for this purpose in Phnom Penh, for instance, was projected to last 25 years but about five years into its use, between 2009 and 2014, about half of the land had been filled already and environmental experts further projected the land to last another five years until 2019 (Sopheap, Inatsu, Thavrak, & Borarin, 2016). Investigations showed that the Cambodian government signed a 50-year contract plan with CINTRI Cambodia Ltd., a private waste management company to take charge of waste collection, management, and disposal.…”
Section: Waste Management and Pollution In Cambodiamentioning
confidence: 99%
“…In fact, soybean has been produced into fermented soybean, commonly called SIENG, and there are two kinds of fermented SIENG in Cambodia, we called SIENG PRAI and SIENG PA-AEM. They are very famous and healthy foods among other Cambodian's soybean processed products [5]. Bacillus subtilis may be present on the soybean seed during cultivation or contaminate in SIENG during process according to Cambodia production context where SIENG is fermented using a pure starter strain of B. subtilis, naturally occurring microorganisms or seeds (a portion of the product) used to produce fermented soybeans in other Asian countries [6].…”
Section: Introduction mentioning
confidence: 99%